Pharmacokinetics of Heparin and Low Molecular Weight Heparin Fragment (Fragmin®) in Rabbits with Impaired Renal or Metabolic Clearance - Palm, M; Mattsson, Ch (Thrombosis and Haemostasis, 1987)
The kinetics and tissue distribution of 3H-heparin and a 3H- labelled low molecular weight heparin fragment were compared in normal rabbits as well as in rabbits with blocked renal function or reticuloendothelial system (RES). Radioactivity in plasma, urine, liver and kidneys, as well as anti-FXa activity in plasma were determined. The plasma elimination of heparin was, when compared to normal controls, prolonged both in rabbits with renal dysfunction as well as in rabbits with blocked RES, while renal dysfunction was the only parameter that significantly prolonged the plasma half-life of Fragmin. Studies on tissue distribution in normal rabbits revealed that about 60 per cent of the radioactive heparin dose accumulated in the liver and kidney three hours after the injection, whereas the corresponding value was less than 10 per cent for the Fragmin-derived radioactivity. The recovery of radioactivity in urine within three hours was 5 and 35 per cent of the dose, respectively, for 3H-heparin and 3H- Fragmin. It is concluded from the present study that the rapid plasma elimination of heparin in the rabbit (tl/2 = 17 minutes) is mainly due to a high tissue distribution (liver and kidney) while the plasma elimination of Fragmin (t1/2 = 28 minutes) is mainly caused by renal excretion.
Keywords: Heparin fragment; Renal clearance; Hepatic clearance